The Student’s Learning Obstacle in Calculus Course - Ria Deswita; Selvia Erita; Febria Ningsih (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2021)
Calculus courses have become the basis of other mathematics courses. However, students often find obstacles in this course that cause low mastery of calculus. Therefore we need an in-depth analysis of students' obstacles in learning calculus to develop proper learning materials and methods. This research aims to analyze the students’ learning obstacles in solving mathematical problems in calculus courses. This research is a qualitative descriptive study. The subjects of this study were first-semester students of the Mathematics Department at one of the Islamic institutes in Jambi, Indonesia. The subject selection technique used is purposive sampling, while the data collection techniques used questionnaires and interviews. Based on data analysis, it was found that there were five types of errors made by students in solving mathematical problems in a calculus course, namely conceptual errors, algorithm errors, calculation errors, algebraic operations errors, and careless errors. Also, there were two types of learning obstacles experienced by students in the calculus course: epistemological obstacles and didactic obstacles. Epistemological obstacles related to conceptual errors, limited understanding of concepts, and errors in analyzing questions. While didactic obstacles related to difficulties in understanding teaching materials and inaccuracy of teaching methods. Further research is needed to overcome learning obstacles that occur in the form of developing appropriate learning materials according to the abilities and characteristics of students and applying appropriate learning models and methods.